Pengaruh Nilai Religiusitas Terhadap Tingkat Depresi Wanita Yang Bekerja Studi Kasus Indonesian Family Life Survey (IFLS) Tahun 2007-2014 - Tarishah Putri Arini; Eva Ervani (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study aims to explore the influence of religiosity on depression levels among working women in Indonesia, using data from the Indonesian Family Life Survey (IFLS) 2007-2014. With the increasing participation of women in the workforce, the challenge of maintaining mental health, particularly depression, becomes increasingly relevant. Employing a quantitative approach and logistic regression analysis, this study examines the relationship between religiosity, socioeconomic variables, and depression levels. The results show that religiosity has a significant positive effect on the probability of not experiencing depression, while age, education, and income also exhibit significant positive influences. Conversely, living in urban areas is found to have a significant negative impact. These findings highlight the importance of religiosity and socioeconomic factors in shaping the mental well-being of working women in Indonesia.